Basic infrastructure and income inequality in Indonesia: a spatial econometrics approach - Abubakar, Ardiansyah; Arifin, Arifin; Muhammad Fadillah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
This study investigates the association between basic infrastructure and income inequality in Indonesia using a spatial panel econometric framework. Based on provincial panel data for 34 provinces from 2015 to 2024, the analysis first documents significant positive spatial dependence in the Gini ratio and then estimates a Spatial Autoregressive Random Effects (SAR-RE) model. The results show a positive, statistically significant spatial autoregressive coefficient (ρ = 0.1926), indicating that provincial inequality is linked to that of neighboring provinces. Better access to clean water and sanitation is associated with lower inequality, with sanitation showing the strongest equalizing effect. By contrast, GRDP continues to have a positive effect, suggesting that regional output expansion alone does not automatically yield inclusive distributional outcomes. This study contributes to the literature by applying spatial panel analysis to Indonesian provinces and by positioning basic infrastructure as an indirect human-capital channel in an archipelagic setting. Although the findings should be interpreted as associative rather than strictly causal, they highlight the importance of cross-provincial coordination in water and sanitation policy to reduce persistent regional inequality.